Associations between polybrominated diphenyl ethers (PBDEs) levels in adipose tissues and female menstrual cycle and menstrual bleeding duration in Shantou, China. (15th May 2022) - Shi, Xiaoling; Wang, Xin; Peng, Lin; Chen, Yebin; Liu, Caixia; Yang, Qingtao; Wu, Kusheng
Abstract: The endocrine-disrupting effects of human exposure to polybrominated diphenyl ethers (PBDEs) have been studied, but their associations with menstrual status were not clearly clarified. This study was to evaluate the associations between PBDE levels in adipose tissues and the menstrual cycle and menstrual bleeding duration alteration. A total of 298 female cases undergoing surgery were recruited from two hospitals in Shantou, China. Demographic, clinical, and pathological information were collected, and adipose tissues were obtained during mammary or abdominal surgery. Gas chromatography with mass spectrometry was used to analyze 14 PBDE congeners in the adipose samples. The associations between PBDE levels and menstrual cycle (MC) and menstrual duration (MD) were analyzed by logistic regression models, estimating odds ratios (ORs) and 95% confidence intervals (CIs). BDE-153 had the highest level in the adipose samples, followed by BDE-209, BDE-183 and BDE-47. Compared with referents, median levels of BDE-47, -71, −153, −183 were higher in women with MC > 30 days (all P  < 0.05); BDE-47, -153, −183, −209 were also higher in women with MD > 5.5 days (all P  < 0.05). After adjusted for age and parity, BDE-47, -71, −153, −183 were associated with prolonged MC (OR = 1.20, 1.15, 1.12, 1.11, respectively, all P  < 0.05) in the logistic regression models; and BDE-47, -153, −183, −209 were associated with the prolonged MD (OR = 1.13, 1.09, 1.10, 1.11, respectively, all P  < 0.05). Several individual PBDE congeners in female adipose were found associated with prolonged menstrual cycle and menstrual duration. PBDEs may influence reproductive health of women by altering menstrual status. Graphical abstract: Image 1 Highlights: PBDE levels in adipose tissues and menstrual characteristics were evaluated. BDE-47, -71, −153, −183 were associated with prolonged menstrual cycle. BDE-47, -153, −183, −209 were associated with the prolonged menstrual bleeding duration. PBDEs may influence reproductive health of women by altering menstrual status.